Mouthwash: A review for South African health care workers - Andre W. van Zyl; Willie F.P. van Heerden (South African Family Practice)
Many conditions within the oral cavity require the use of a mouthwash. This can vary from breath fresheners to treatment of life threatening secondary infections such as oral mucositis in patients undergoing bone marrow transplant therapy. The use of mouthwashes requires a correct diagnosis of the oral condition and a thorough knowledge of the product in question to achieve effective treatment. It is the objective of this review to help health care workers in South Africa make the correct choice of treatment when dealing with diverse conditions of the oral cavity.